A novel surface-enhanced Raman scattering probe based on Au nanoboxes for dynamic monitoring of caspase-3 during cervical cancer cell apoptosis. Issue 2 (7th December 2020) - Sun, Yue; Wang, Youwei; Lu, Wenbo; Liu, Chang; Ge, Shengjie; Zhou, Xinyu; Bi, Caili; Cao, Xiaowei
Abstract : The highly sensitive and reliable detection, imaging, and monitoring of changes of intracellular caspase-3 are critical for understanding the cell apoptosis and studying the progression of caspase-3-related cervical cancer. Abstract : The highly sensitive and reliable detection, imaging, and monitoring of changes of intracellular caspase-3 are critical for understanding the cell apoptosis and studying the progression of caspase-3-related cervical cancer. Herein, we present a novel surface-enhanced Raman scattering (SERS) probe for the detection of caspase-3 during cervical cancer cell apoptosis, composed of Au nanoboxes modified with Nile blue A as a Raman reporter and a caspase-3-specified peptide as a molecular cross-linker. In the presence of caspase-3, the substrate peptides can be cleaved and the changed surface charge of the Au nanoboxes results in the Au nanoboxes–NBA–peptide assembling to form aggregates and a great enhancement of SERS signal. The finite-difference time-domain simulation showed that hot spots mainly located in the nanogaps of the aggregated Au nanoboxes, which in theory proved the rationality of this signal amplification method. The SERS probes exhibited excellent reproducibility and selectivity toward caspase-3. A detection limit of 0.127 fM was obtained for caspase-3, with a dynamic range from 1 fM to 1 nM. MTT assay demonstrated that the probes had no obvious cytotoxicity within a certain concentration range. HeLa cells were treated with doxorubicin to induce long-term apoptosis. Upon cellular uptake of these probes, the spatiotemporal dynamics of caspase-3 in apoptotic cells could be real-time monitored using SERS. The activity of caspase-3 increased with the prolongation of apoptosis time. The SERS results were in accordance with that of western blotting assay. This kind of probe can offer great potential for the determination of enzymatic activities in the physiological processes of cells.